Analisis Kesetaraan Gender di Pedesaan (Studi Kasus Petani Tanaman Hias di Kampung Wisata Sewu Kembang) - Naning Dyah Pitaloka; Eksa Rusdiyana; Widiyanto Widiyanto (Universitas Sebelas Maret, 2024)
The principle of sustainable management of natural resources is equality. Equality comes not only from the roles of different interest groups but also from gender equality. This research aims to analyze the impact of developing tourist villages on gender equality. The basic method in this research is qualitative, using a case study approach. The gender analysis model used in this research is the Gender Analysis Matrix (GAM). The research location was selected purposively, and informants were selected using purposive sampling and snowball sampling. Research data was obtained by interviews, observation and documentation. Data analysis was carried out by means of data reduction, data presentation, data interpretation, and conclusions drawing. The validity of the data used is triangulation of sources and techniques. The results of this research show that men and women have their respective roles in the aspects of labor, time, resources and social culture. The development of tourism villages has not achieved gender equality because women’s positions are still weak in community institutions. There is a need for public awareness to improve institutions, so that men and women obtain equal positions in deliberations and management of the institution itself.